Research data management survey: report - Parsons, Thomas; Grimshaw, Shirley; Williamson, Laurian (The University of Nottingham, 2013)
A summary of findings and results from The University of Nottingham 2012 Research Data Management survey. This work was produced as part of the JISC funded ADMIRe Managing Research Data project.